2002
DOI: 10.1007/s00422-001-0293-y
|View full text |Cite
|
Sign up to set email alerts
|

New attractor states for synchronous activity in synfire chains with excitatory and inhibitory coupling

Abstract: In a feedforward network of integrate-and-fire neurons, where the firing of each layer is synchronous (synfire chain), the final firing state of the network converges to two attractor states: either a full activation or complete fading of the tailing layers. In this article, we analyze various modes of pattern propagation in a synfire chain with random connection weights and delta-type postsynaptic currents. We predict analytically that when the input is fully synchronized and the network is noise free, varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…In contrast, nontrivial limit cycles or chaotic activity was not observed in the current model. The results of Yazdanbakhsh et al (2002) are consistent with a stochastic steady state, which they failed to discriminate from chaotic activity. Note that the extrapolation of the transfer function in the lower range of input (that is, when 0 < n µ−1 < 1) used in their model is not realistic.…”
Section: Dynamics Of Randomly Connected Network With Inhibitory Couplingsupporting
confidence: 86%
See 1 more Smart Citation
“…In contrast, nontrivial limit cycles or chaotic activity was not observed in the current model. The results of Yazdanbakhsh et al (2002) are consistent with a stochastic steady state, which they failed to discriminate from chaotic activity. Note that the extrapolation of the transfer function in the lower range of input (that is, when 0 < n µ−1 < 1) used in their model is not realistic.…”
Section: Dynamics Of Randomly Connected Network With Inhibitory Couplingsupporting
confidence: 86%
“…The transition matrix may have a characteristic period of two. Yazdanbakhsh et al (2002) have reported simulation results that seem to indicate chaotic and quasiperiodic activity in this regime. In contrast, nontrivial limit cycles or chaotic activity was not observed in the current model.…”
Section: Dynamics Of Randomly Connected Network With Inhibitory Couplingmentioning
confidence: 91%
“…Macroscopic chaos mentioned above arises from the network's global properties, the 306 propensity of isolated neurons to oscillate, the nature of synaptic dynamics, or a 307 mixture of the them, as shown in earlier works [25][26][27][28][29]. In this paper, the focus is 308 different.…”
mentioning
confidence: 88%
“…More recently, a totally different mechanism showed that asynchronous 22 chaos, where neurons exhibit asynchronous chaotic firing-rate fluctuations, emerge 23 generically from balanced networks with multiple time scales synaptic dynamics [20]. 24 Different modeling approaches have been used to uncover important conditions for 25 observing these types of chaotic behavior (in particular, synchronous and asynchronous 26 chaos) in neural networks, such as the synaptic strength [25][26][27] in a network, 27 heterogeneity of the numbers of synapses and their synaptic strengths [28,29], and lately 28 the balance of excitation and inhibition [21] . The results obtained by Sompolinsky et 29 al.…”
mentioning
confidence: 99%
See 1 more Smart Citation